Pengaruh Institutional Trust terhadap Perilaku Kooperatif dalam Penerapan Protokol Kesehatan Pandemi Covid – 19 - Shofa Salsabila Farhah; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2022)
Abstract. Covid-19 began to spread throughout the world, including in Indonesia, the government then provided preventive measures in dealing with this new variant of the virus by urging the public to obey the health protocols that have been set to reduce the rate of spread. However, there are still many omissions made by the community against these recommendations so that students in this case have a role in educating the public about this, especially students of the medical faculty which are engaged in the medical and health fields. The purpose of this study was to determine the effect of institutional trust on student cooperative behavior in the application of health protocols to students of the Faculty of Medicine in Bandung City during the COVID-19 pandemic. This study uses a quantitative approach with a non-experimental causality research design that combines convenience sampling with snowball sampling with a total of 170 students from the Faculty of Medicine in Bandung. The analytical technique used is the Simple Linear Regression Test using SPSS software. From the results of data analysis shows that there is an influence of institutional trust on the cooperative behavior of Medical Faculty students in Bandung. Statistical analysis shows the value of the coefficient of determination shows the results of 0.027 or an influence of 2.7%. Abstrak. Abstrak— Covid – 19 mulai menyebar ke seluruh dunia termasuk di Indonesia, pemerintah lalu memberikan upaya – upaya pencegahan dalam menangani virus varian baru ini dengan menghimbau masyarakatnya untuk mentaati protocol kesehatan yang telah ditetapkan untuk menurunkan laju penyebaran. Namun masih banyaknya kelalaian yang dilakukan oleh masyarakat terhadap anjuran tersebut sehingga mahasiswa dalam kasus ini memiliki andil untuk mengedukasi masyarakat mengenai hal ini, terlebih mahasiswa fakultas kedokteran yang dimana bergerak di bidang medis dan kesehatan. Tujuan dari penelitian ini adalah mengetahui pengaruh institutional trust terhadap perilaku kooperatif mahasiswa dalam penerapan protokol kesehatan pada Mahasiswa Fakultas Kedokteran di Kota Bandung selama masa pandemi covid – 19. Penelitian ini menggunakan pendekatan kuantitatif dengan disain penelitian kausalitas non eksperimental yang mengkombinasikan convinience sampling dengan snowball sampling dengan jumlah responden sebanyak 170 Mahasiswa Fakultas Kedokteran di Kota Bandung. Teknik analisis yang digunakan adalah Uji Regresi Linier Sederhana dengan menggunakan software SPSS. Dari hasil analisis data menunjukkan bahwa terdapat pengaruh institutional trust terhadap perilaku kooperatif Mahasiswa Fakultas Kedokteran di Kota Bandung. Analisis statistik menunjukkan nilai koefisien determinasi menunjukkan hasil 0.027 atau mempengaruhi sebesar 2.7%.